Transcriptome Analysis Revealed Potential Mechanisms of Resistance to Trichomoniasis gallinae Infection in Pigeon (Columba livia) - Yuan, Jingwei; Ni, Aixin; Li, Yunlei; Bian, Shixiong; Liu, Yunjie; Wang, Panlin; Shi, Lei; Isa, Adamu Mani; Ge, Pingzhuang; Sun, Yanyan; Ma, Hui; Chen, Jilan (Frontiers in Veterinary Science, 2021)
Trichomoniasis gallinae (T. gallinae) is one of the most pathogenic parasites in pigeon, particularly in squabs. Oral cavity is the main site for the host-parasite interaction. Herein, we used RNA-sequencing technology to characterize lncRNA and mRNA profiles and compared transcriptomic response of squabs, including four susceptible birds from infected group, four tolerable birds without parasites after T. gallinae infection, and three birds from uninfected group, to understand molecular mechanisms underlying host resistance to this parasite. We identified 29,809 putative lncRNAs and depicted their genomic features subsequently. Differentially expressed (DE) genes, DE-lncRNAs and cis/trans genes of DE-lncRNAs were further profiled among three groups. The KEGG analysis indicated that specific intergroup DE genes were involved in focal adhesion pathway, whereas the cis/trans genes of DE-lncRNAs were enriched in cytokine-cytokine receptor interaction, toll-like receptor signaling pathway, p53 signaling pathway and insulin signaling pathway, suggesting that lncRNAs may affect T. gallinae invasion in pigeon mouth through their target genes. Moreover, co-expression analysis identified integrated lncRNA-gene interaction networks. Several DE-lncRNAs including MSTRG.68052.50, MSTRG.82272.3, MSTRG.114849.42, MSTRG.153522.2 and MSTRG.84452.20 were interacted with methylation and immune-related genes, such as TMRT10C, JCHAIN, IL18BP, ANGPT1, SAMD9L and SOCS3, implying that DE-lncRNAs exert critical influence on T. gallinae infections. The quantitative exploration of host transcriptome changes induced by T. gallinae infection broaden both transcriptomic and epigenetic insights on T. gallinae resistance and its pathological mechanism. Candidate genes and lncRNAs would be further verified and applied to future selection and breeding for disease resistance birds.